On the Issue of the Concept and Status of Minors in Constitutional Law and Current Problems of the Implementation of the Rights and Freedoms of Minors - ABIKENOVA, Gulzhan; KUBEYEV, Yerkin; BOZHKARAULY, Altai; ABDIKEEV, Marat; RUSTEMBEKOVA, Dinara (Journal of Advanced Research in Law and Economics; Vol 9 No 3(33) (2018): JARLE, Volume IX, Issue 3(33), Summer 2018DO - 10.14505/jarle.v9 3(33).02, 2018)
An indicator of the acquisition by the Republic of Kazakhstan of the status of a legal democratic state is the real-value attitude of the state to a person, his rights and freedoms, taking into account the specifics of their various categories and groups, including minors. On the one hand, the future of any state is objectively associated with minors; on the other hand, they are defenseless due to complete or partial physical, mental, social immaturity. Therefore, the problems of childhood, the protections of the rights of minors are in the spectrum of priority both for our state and for other countries of the world community. The Constitution of the Republic of Kazakhstan enshrines the legal status of a person and a citizen of the Republic of Kazakhstan, recognizes and guarantees the inalienability of fundamental rights and freedoms imposes the duty of the state to support family, motherhood, fatherhood and childhood. At the same time, in modern Kazakhstan there is a contradiction between the constitutional nature of the system for protecting the rights of minors and its actual functioning. As a result, there arises the need of society to create an effective mechanism for the implementation of constitutional guarantees of the rights and legal interests of minors.